Recent advances in the ultraviolet protection finishing of textiles - Zala Mavrić; Brigita Tomšič; Barbara Simončič (Tekstilec, 2018)
This paper reviews the recent research in the field of application of ultraviolet (UV) protection finishes in textile functionalisation. The aim and the UV protecting mechanisms of UV protection finishes on textile substrates are described. The standard methods for determination of UV protective properties are presented. Contemporary research directions in the application of environmentally friendly organic UV absorbers and inorganic UV blockers are highlighted and discussed. The bioactive substances as novel organic UV absorbers are exposed. Novel multifunctional properties of textiles including the inorganic UV blockers are described. The ecological issues of the use of UV protection finishes are presented.